Governmentality Practices in Community Empowerment: One Step to Create Economic Income and Social Protection in Pematang Johar Village, Deli Serdang Regency - Mujahiddin, Mujahiddin; Badaruddin, Badaruddin; Lubis, Zulkifli; Daulay, Harmona (PT. Riset Press International, 2024)
Linking governmentality practices to community empowerment programs in rural areas is based on the Indonesian government's claim that the success of development in villages is due to the involvement of the central government in directing development planning in villages through the various technical regulations they issue. Village governments are only given space for elaboration and accommodation of regulations made by the central government based on local values, local potential, needs and interests of village communities. The existence of this space for elaboration and accommodation makes the practice of governmentality applicable in rural areas, namely giving freedom and authority to villages but at the same time directing them with various possible choices that are actually desired by the state. This article finds the operation of governmentality practices in the discourse of increasing economic welfare rationalized by the Pematang Johar Village Government for the community through the development of rice field tourism objects in their village. This discourse is able to change the village community's perception of the goals of village development, which until now have only been understood in terms of infrastructure development. Through this discourse, the village government is able to form empowered people; namely village people who are continuously trained in skills, corrected and disciplined. The self-adaptation that they carry out is of course aimed at increasing their capacity and quality from the status of the tasks they carry out daily in the rice field tourism which leads them to become economically prosperous.